Interaction between the C. elegans centriolar protein SAS-5 and microtubules facilitates organelle assembly - Bianchi, S; Rogala, KB; Dynes, NJ; Hilbert, M; Leidel, SA; Steinmetz, MO; Gönczy, P; Vakonakis, I (American Society for Cell Biology, 2018)
Centrioles are microtubule-based organelles that organise the microtubule network and seed the formation of cilia and flagella. New centrioles assemble through a step-wise process dependent notably on the centriolar protein SAS-5 in Caenorhabditis elegans. SAS-5 and its functional homologues in other species form oligomers that bind the centriolar proteins SAS-6 and SAS-4, thereby forming an evolutionarily conserved structural core at the onset of organelle assembly. Here, we report a novel interaction of SAS-5 with microtubules. Microtubule binding requires SAS-5 oligomerisation and a disordered protein segment that overlaps with the SAS-4 binding site. Combined in vitro and in vivo analysis of select mutants reveals that the SAS-5–microtubule interaction facilitates centriole assembly in C. elegans embryos. Our findings lead us to propose that the interdependence of SAS-5 oligomerisation and microtubule binding reflects an avidity mechanism that strengthens SAS-5 associations with other centriole components and, thus, promotes organelle assembly.